Risky journeys – Risk and decision-making among potential irregular migrants in Senegal and Guinea - Jasper Tjaden (International Migration, 2022)
In response to well-documented harms inflicted on irregular migrants attempting to travel from West Africa to Europe, various actors have scaled up information interventions to counter misinformation by smuggling networks and facilitate safe migration decisions. Many interventions include information on the potential dangers involved in migration. However, there is a striking lack of empirical evidence assessing a key assumption of campaign effectiveness, that is the relationship between risk perceptions and the decision to migrate irregularly. This study contributes an empirical account based on two independently collected surveys in Senegal and Guinea. Consistent with rational choice theories on migration decisions under uncertainty, the results suggest that higher risk perceptions are consistently and strongly associated with reduced intentions to migrate irregularly. Yet, the explanatory power of risk perceptions depends on context and is generally less important than structural and socio-economic factors.
Keywords: 300